TEACHING READING USING MAGAZINE - Henny Uswatun Hasanah (OKARA: Jurnal Bahasa dan Sastra, 2013)
Teaching is a process of communication. It has to be created through the way of teaching and exchanging the message or information by every teacher and student. The message can be knowledge, skills, ideas, experiences, and many others. Through the process of communication, the people can receive the message or information. To avoid misunderstanding in the process of communication, media are needed in the process of teaching. Magazine can be other alternative as reading material in the classroom. Magazine as reading material has appeal for the students. To make the students get information from magazine, the teacher can ask the students to observe table of content and giving the students training to use it. Like, what is done on text book. Distinguishing informative reading material with fictive reading, important to know students in reading magazine. Like analyzing advertisements to detect propaganda.